Effect of the knockdown of Cabin1 on p53 in glomerular podocyte. (3rd March 2016) - Wen, Yueqiang; Zhou, Peilan; Liu, Lingling; Wang, Zebin; Zhang, Yajie; Liang, Jianbo
Abstract: Calcineurin binding protein 1 (Cabin1) is a natural inhibitor of calcineurin (CN). Moreover, Cabin1 retards tumor cell apoptosis by regulating p53. This study was designed to observe the expression of Cabin1 during podocyte injury, as well as its relationship with p53. Sprague-Dawley rats were used for the establishment of 5/6 nephrectomized rat model. Sham-operated rats underwent ventral laparotomy without nephrectomy. Then, rats were sacrificed at 8 and 12 weeks after nephrectomy. WT-1, a podocyte nuclear protein, was used for indicating the localization of Cabin1 in glomeruli. As tacrolimus protects podocyte via inhibiting AngiotensinII (AngII) induced CN activation. Cultured podocytes were injured by AngII or restored by tacrolimus. The protein expression and localization was detected by western blot or immunofluorescence staining. Cabin1 was knocked down by siRNA in cultured podocytes. In 5/6 nephrectomized rats, the colocalization of Cabin1 and WT-1 became more obviously in podocyte nuclei. Cabin1 protein was markedly increased in rats at 8 and 12 weeks after nephrectomy, as well as in AngII injured podocytes at 48 h (0.99 ± 0.12 in AngII group versus 0.80 ± 0.16 in control group). Cabin1 and p53 colocalized in cultured podocyte nuclei, p53 expression was significantly decreased (0.21 ± 0.05 in siRNA group versus 0.31 ± 0.05 in negative control group) after Cabin1 was being knocked down. In conclusion, Cabin1 expression significantly increases during podocyte injury. Knockdown of Cabin1 induces p53 expression decrease in cultured podocyte. Cabin1 may provide a new target to investigate podocyte injury.